2009
DOI: 10.1677/jme-08-0189
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and telomerase in adrenocortical tissue maintenance, carcinogenesis, and aging

Abstract: Telomere dysfunction and telomere maintenance mechanisms contribute to major steps of carcinogenesis. Dysfunctional telomeres lead to the generation of genomic aberrations, such as amplifications and deletions. Telomere maintenance mechanisms, such as telomerase activity and alternative telomere lengthening, provide the basis of malignant cell expansion independent of telomere shortening-induced apoptosis or senescence, ensuring tumor survival. Recent advances highlight the importance of these mechanisms in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 116 publications
1
8
0
Order By: Relevance
“…In this study, we expanded the spectrum of TERT promoter-mutated tumors to ACCs, ea PGLs, and GISTs, while adding TERT promoter mutations to other mechanisms of TERT mRNA upregulation in adrenocortical tumorigenesis (Else et al 2008, Else 2009) consistent with previously reported associations in other tumor types (Arita et al 2013, Tallet et al 2013, Vinagre et al 2013. Interestingly, we found that two ea PGLs of urinary bladder harboring TERT promoter mutations were SDHdeficient tumors.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we expanded the spectrum of TERT promoter-mutated tumors to ACCs, ea PGLs, and GISTs, while adding TERT promoter mutations to other mechanisms of TERT mRNA upregulation in adrenocortical tumorigenesis (Else et al 2008, Else 2009) consistent with previously reported associations in other tumor types (Arita et al 2013, Tallet et al 2013, Vinagre et al 2013. Interestingly, we found that two ea PGLs of urinary bladder harboring TERT promoter mutations were SDHdeficient tumors.…”
Section: Discussionsupporting
confidence: 71%
“…Critical shortening of telomeres causes an arrest of the cell division cycle and induce cellular senescence or apoptosis [135,136]. Although in many proliferating tissues telomeres shorten with each cell division, telomere length unusually increases with aging in spermatozoa [133].…”
Section: Telomeresmentioning
confidence: 99%
“…Telomerase prevents shortening of telomeres by providing a template of TTAGGG sequences at the end of the telo-mere, allowing extension in the 5′-3′ direction. The activity of telomerase is considered a marker of human stem cells, and telomerase expression is found by radioactive in situ method in the outer cortex of the adrenal, labeling a putative adrenal stem cell population (Else, 2009; Yashima et al, 1998). Moreover, studies in various mouse models (Bayne et al, 2008) reveal that telomere length is longest in the peripheral cortex, suggesting that telomerase is active in a population of the zG.…”
Section: Telomeres Tert and Terf2 Expressionmentioning
confidence: 99%